Determinação de hormônios estrogênios em água por cromatografia : uma revisão crítica de métodos analíticos - Nascimento, Marília Souza do (2015)
Estrogens (female sex hormones) belong to the emerging contaminants group that comprises hydrophobic organic compounds with low volatility which have been found in water in the natural (17β-estradiol (E2), estriol (E3), estrone (E1)) and/or synthetic form (17α-ethynilestradiol (EE2)) used in the formulation of contraceptive medicines. As a recent research field, there are few published national studies concerning the analysis of these contaminants in natural waters and so far, there is no specific legislation governing the issue of hormones in the environment or establishing maximum limits for such compounds. Contamination sources include urine excreted by humans and mammals in wastewater and can be found in surface water, sewage, wastewater, meat, milk and dairy products. Thus, it is important to monitor these agents. Due to the complexity of environmental matrices (physiologically active) and the very low concentrations which occur in the environment, for environmental monitoring, it is necessary to use sensitive and selective analytical methods which, in general, envolve tedious and laborious procedures. Methods reported in the literature consist on the extraction of the analytes from the matrix, followed or not by derivatization, with identification and quantification by chromatography. Regarding extraction procedures, solid phase extraction (SPE) with different adsorbents is the most frequently used method due to the high concentration factor that can be achieved with this procedure. However, other extraction procedures have been reported recently. Techniques such as solid- or liquid-phase micro-extraction, stirring bar sorptive extraction (SBSE) or the use of nanoparticles as solid phase have been reported presenting the advantage of being easy, requiring little sample manipulation as well as producing less waste residues. Analytes derivatization is necessary when gas chromatography is used due to their low volatility and the presence of hydroxyl groups that cause peak tailing. Silylation with different derivatizing agents is the mostly used reaction but several authors reported problems such as incomplete reaction and formation of by-products that need to be carefully controlled. In relation to the chromatographic techniques, gas or liquid chromatography coupled to mass spectrometry is the mostly used one. Gas chromatography, despite needing derivatization of the estrogens, has the advantage of having more resolution and high sensitivity. On the other hand, the modern equipment of ultra-performance liquid chromatography tandem mass spectrometry have allowed the achievement of very low detection limits also with this technique. However, the high cost of this equipment is still a limiting factor for its most widely use. Therefore, it is still necessary to develop low cost sensitive techniques to allow the continuous monitoring of these hormones.